The Doctor, the Lawyer, and the Melancholy Witch - Migliore, Sam (Anthropologica, 2022)
During the sixteenth and seventeenth centuries, a great number of individuals were accused, tried, and in many cases, killed as witches. Scholars agree that the witch craze was possible because the learned professions, including medicine, could not provide a convincing "natural" explanation for witchcraft phenomena. However, dissent from the orthodox view of witchcraft did exist. The Dutch physician Johann Weyer (Wier) provided a logical explanation, based on accepted medical beliefs of the period, for the voluntary confessions of suspected witches. This paper examines a number of complex factors which made the acceptance of Weyer’s "natural" explanation problematic. Stated simply, Weyer failed to convince others to accept his explanation because he presented a new idea within the constraints of an old system. This allowed the French philosopher Jean Bodin to manipulate various ambiguities and inconsistencies in the Galenic medical system, and to use these inconsistencies to counteract Weyer’s argument.